Selection of stock markets: a factor analysis approach. (22nd January 2010) - Hui, Tak Kee; Tsui, Kai Chong; Chua, David
This study uses factor analysis to simplify the complex relationships among stock markets and to reduce the number of markets required for portfolio construction. Our sample consists of the US and 11 Asia-Pacific stock markets. We find that the reduced portfolio obtained from factor analysis has the same return per unit risk as that constructed with all 12 stock markets. Sub-periods, pre-crisis and post-crisis periods are also examined. Comparisons of optimal portfolios reveal that the exclusion of dividends understates the benefits of diversification and has an influence on optimum portfolio selection and country weights.